A Evaluasi Pengadaan Laptop Ber-TKDN dalam Meningkatkan Value for Money dan Pengembangan Produk Dalam Negeri - Dharmayanti, Indrani; Palinrungi, Muhammad Kahar Akbar; Aryati, Aster; Nursyanti, Yevita (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2025)
The government’s procurement of laptops is now required to use domestically manufactured products. For process efficiency, procurement consolidation is achieved using an electronic catalog. The research aims to evaluate the effectiveness and efficiency of the TKDN laptops procurement through the national consolidation program, identify factors influencing the effectiveness and efficiency, and analyze user perceptions of the quality and performance of the products. The study employs perception analysis, which is processed and presented using descriptive statistics. The findings indicate that the consolidated procurement of domestically produced laptops is relatively effective, as it meets most organizational needs, although some laptop specifications (e.g., processor, RAM, and HDD) remain inadequate. Consolidation is also more efficient than individual procurement, because it determines the upper price limit, and allows it to be negotiated during the transaction. Best value for money has been obtained in terms of supply quantity, delivery time and location, price and service provider. But there are still complaints about quality. Factors that influence procurement effectiveness include identifying needs, determining specifications and negotiating prices, as well as monitoring and reporting deviations during implementation.